Virulence Gene Expression of Staphylococcus aureus in Human Skin - Cruz, Ana Rita; van Strijp, Jos A. G.; Bagnoli, Fabio; Manetti, Andrea G. O. (Frontiers in Microbiology, 2021)
Staphylococcus aureus is the main cause of human skin and soft tissue infections. However, S. aureus pathogenicity within the skin is not fully characterized. Here, we implemented an S. aureus cutaneous infection model using human skin explants and performed a time-course infection to study the gene expression profile of a large panel of virulence-related factors of S. aureus USA300 LAC strain, by high-throughput RT-PCR. We pinpointed the genes that were differentially regulated by the bacteria in the skin tissues and identified twelve virulence factors that were upregulated at all time points assessed. Finally, using confocal microscopy, we show that the expression of alpha-hemolysin by S. aureus varies dependent on the skin niche and that the bacteria preferentially accumulates inside sweat glands and ducts. Taken together, our study gives insights about the pathogenic lifestyle of S. aureus within human skin tissues, which may contribute for the development of anti-S. aureus therapeutic strategies.